Nilai Moral Bagi Kalangan Muda Dalam Mempergunakan Internet - Irma Rahmi Oktaviani; Muhamad Abil Fachrizal; Ayang Nurmelisa Putri; Mochamad Dimas Nurhaadiiansyah (IHSA Institute, 2022)
Internet makes it easy for people, especially young people to communicate. Advances in Internet technology and mobile phones, social media is also growing rapidly. Young people in the modern era are proficient in managing and utilizing computer technology in using the Internet. The modern era can be said to be an era where there is a lot of development, be it the development of culture, the development of education and technology. It is very regrettable if the use of the internet even make the younger generation has no moral value in itself. Therefore, in order that moral values are always used young people to use the internet there are some that can be considered and applied ie, embedding religious values, raise the awareness of young people and the role and improve discipline.